Alloantibody Generation and Effector Function Following Sensitization to Human Leukocyte Antigen - Hickey, Michelle J.; Valenzuela, Nicole M.; Reed, Elaine F. (Frontiers in Immunology, 2016)
Allorecognition is the activation of the adaptive immune system to foreign Human Leukocyte Antigen (HLA) resulting in the generation of alloantibodies. Due to a high polymorphism, foreign HLA is recognized by the immune system following transplant, transfusion or pregnancy resulting in the formation of the germinal center and the generation of long lived alloantibody producing memory B cells. Alloantibodies recognize antigenic epitopes displayed by the HLA molecule on the transplanted allograft and contribute to graft damage through multiple mechanisms including 1) activation of the complement cascade resulting in the formation of the MAC complex and inflammatory anaphylatoxins, 2) transduction of intracellular signals leading to cytoskeletal rearrangement, growth and proliferation of graft vasculature, and 3) immune cell infiltration into the allograft via FcR interactions with the FC portion of the antibody. This review focuses on the generation of HLA alloantibody, routes of sensitization, alloantibody specificity and mechanisms of antibody-mediated graft damage.